Protection against inhalation anthrax by immunization with Salmonella enterica serovar Typhi Ty21a stably producing protective antigen of Bacillus anthracis - B. Kim Lee Sim (Nature Portfolio, 2017)
Counterterrorism: creating a safe, stable, easily stored anthrax vaccine A vaccine candidate for anthrax infection shows promise for improving preparedness for a biological attack. Bacillus anthracis, the bacterium responsible for anthrax is a top-tier bioterrorism agent due to its high lethality and spore stability. The current FDA-approved anthrax vaccine and other vaccine candidates in development lack ease of preparation, have short shelf lives and adverse effects. B. Kim Lee Sim of Protein Potential LLC and her collaborators combined key B. anthracis genetic material into an existing typhoid vaccine. The vaccine vector possesses high stability, a strong safety record, and offers long-term protection after oral administration, which Sim’s group hopes to preserve in their candidate anthrax vaccine. The team showed that their hybrid vaccine conferred excellent protection in rabbits and a short vaccination regimen, and suggest further studies into its suitability for human vaccine studies.